2006
DOI: 10.1007/s11249-006-9138-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface treatment on the mechanical and tribological performance of Kevlar pulp reinforced epoxy composites

Abstract: Solutions of rare earth modifier (RES) and epoxy chloropropane (ECP) grafting modification method were used for the surface treatment of Kevlar pulp. The surface characteristics of untreated and treated Kevlar pulp were characterized by Fourier transform infrared (FT-IR) spectroscope. The bend strength and block-on-ring wear behavior of Kevlar pulp/epoxy composites were comparatively investigated. The worn surfaces of the composites were examined by scanning electron microscope (SEM). The results show that sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The FT‐IR transmittance spectra of AP, before and after the IL treatments, are shown in Figure . All of them show the three characteristic aramid peaks, at 3300 cm −1 (NH stretching vibrations in a secondary amide in trans form with a bonded hydrogen), 1640 cm −1 (amide CO stretching for hydrogen‐bonded amide groups), and 1540 cm −1 (NH group) . The absence of IL‐related peaks and wavenumber shifts in the AP‐related peaks suggests that only a minor part of the IL was adsorbed on the outer surface and that the IL was probably mainly located within the AP bundles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FT‐IR transmittance spectra of AP, before and after the IL treatments, are shown in Figure . All of them show the three characteristic aramid peaks, at 3300 cm −1 (NH stretching vibrations in a secondary amide in trans form with a bonded hydrogen), 1640 cm −1 (amide CO stretching for hydrogen‐bonded amide groups), and 1540 cm −1 (NH group) . The absence of IL‐related peaks and wavenumber shifts in the AP‐related peaks suggests that only a minor part of the IL was adsorbed on the outer surface and that the IL was probably mainly located within the AP bundles.…”
Section: Resultsmentioning
confidence: 99%
“…All of them show the three characteristic aramid peaks, at 3300 cm −1 (N H stretching vibrations in a secondary amide in trans form with a bonded hydrogen), 1640 cm −1 (amide C O stretching for hydrogen-bonded amide groups), and 1540 cm −1 (N H group). 19,20 The absence of IL-related peaks and wavenumber shifts in the AP-related peaks suggests that only a minor part of the IL was adsorbed on the outer surface and that the IL was probably mainly located within the AP bundles. Regarding the IL analyses, spectral bands in the 3200-3000 cm −1 region were attributed to coupled aromatic C-H stretching vibrations of the imidazolium ring, and those within 3000-2850 cm −1 were assigned to the aliphatic C-H stretches of the CH 2 and CH 3 groups of the butyl or carboxymethyl chains.…”
Section: Resultsmentioning
confidence: 99%
“…Other tests were also performed to evaluate the surface treatment of AP, however, TGA traces did not confirm the theoretical IL‐contents of 0.5, 1.0, and 2.0 wt %. The FTIR transmittance spectra of the AP before and after the IL treatments are shown in Figure , and they show the three characteristic aramid peaks at 3300 (NH stretching vibrations in a secondary amide in trans form with a bonded hydrogen), 1640 (amide CO stretching for hydrogen‐bonded amide groups), and 1540 cm −1 (NH group) . FTIR analyzes of the IL showed spectral bands in the 3200–3000 cm −1 region attributed to the coupled aromatic CH stretching vibrations of the imidazolium ring, while those within 3000–2850 cm −1 can be assigned to the aliphatic CH stretches of the CH 2 and CH 3 groups of the butyl chains.…”
Section: Resultsmentioning
confidence: 99%
“…In ECH grafting surface modification, the Kevlar fabric was initially immersed in a solution of KOH (1%) at room temperature for 2 h, followed by washing with distilled water and dried for 48 h at room temperature. It is the initiator for grafting with ECP and hydrolyzation of the amino bond and -COOK groups were introduced onto the Kevlar fibre surface, after which Kevlar fibre was grafted in ECP at 80 • C for 6 h. During surface modification treatment, acetone was added with ECH to prevent the drastic reaction, then washed with distilled water and dried in a vacuum oven [28,29].…”
Section: 2d Ech Treatment (Te Treatment)mentioning
confidence: 99%
“…Liu et al have reported that the interfacial strength, wear strength and bending strength were improved in modified Kevlar/epoxy composites by treating with epoxy chloropropane (ECP) [28,29]. Mckelvey et al have indicated that the better dry crew resistance in cellulose fibre was achieved by treating with epichlorohydrin (ECH) at 80 • C after pretreatment with concentrated solutions of basic salts [30].…”
Section: Introductionmentioning
confidence: 99%